Pencarian Data Dengan Indeks Takterurut Menggunakan Algoritma Kuantum - Freddy P. Zen; Ardian Nata Atmaja; Susanto Sigit (Institut Teknologi Bandung, 2003)
This paper will discuss about Grover algorithm for searching a record in a database. There is only one way to search a record in a database with N unordered indices, which is by checking each index and comparing with the record that will be searched. This classical algorithm uses an oracle as much O(N). By using Grover algorithm and quantum parallelism, which will solve the searching problem with uses an oracle as much O(vN) . Grover algorithm is more efficient compared to the classical algorithm if the N number is bigger.